Characterization, differentiation and therapeutic application of NG2+ progenitor cells - Ju, Pei Jun (2013)
The widespread NG2-expressing cells in the central nervous system (CNS) are considered as heterogeneous populations with plastic lineage potential. They rapidly proliferate and differentiate in response to CNS injuries, thereby possessing a therapeutic potential.